A method engineering perspective for service-oriented system engineering. Issue 4 (16th November 2015) - Gherib, Boutheina; Baghdadi, Youcef; Kraiem, Naoufel
Abstract : Purpose: – The purpose of this paper is to consider the method engineering perspective for service-oriented system engineering (SOSE). A number of SOSE methods have been proposed in both academia and industry. Given this, many intuitive, common questions arise. To answer these questions, many comparison frameworks have been developed. Each of which has considered certain methodological perspectives. However, less attention has been given to the method engineering (ME) perspective. The authors argue that this perspective would answer the question "what ME to apply in order to produce SOSE methods that themselves produce quality services at different levels of abstraction and SBAs". This research question is further decomposed into other questions; the main one is "whether the existing ME do apply to service orientation". Answering such a question would lead to either developing SOSE methods by using the existing ME or developing a new ME or framework for the specifics of SOSE. Design/methodology/approach: – This work first provides a literature review on ME approaches and techniques; then, it compares a sample of existing SOSE methods with respect to their ME within a comparison framework that comprises a set of relevant properties of a solution that would be provided by an SOSE method, namely, service-oriented architecture (SOA) adoption, quality of services and ME; and finally, it discusses the applicability of the existing ME to SOSE. Findings: – Strengths and weaknesses of the existing methods with respect to the aforementioned criteria, in addition to SOSE methodology open issues, were identified. The comparison has shown that while the existing SOSE methods have proved their success in a specific task, they still present some weaknesses. Therefore, it is better to benefit from the advantages of the existing ME techniques, notable method fragments, even if they need some alteration. Research limitations/implications: – While this work has many open issues related to SOSE methods with respect to ME, it could be further developed in many directions by exploring the open issues. For instance, the generation of a new ME technique and application of this new ME technique to the existing SOSE methods to see to what extent the existing methods may be situational. Practical implications: – This work has practical implications, as it provides a better understanding of different views of SOSE methods, and assists the method engineers in deciding which ME technique is most suitable to their situation. Social implications: – The produced artifact provides a research roadmap toward SOSE ME. Originality/value: – None of the existing comparison frameworks for SOSE methods has considered the criteria such as SOA adoption and ME techniques. Indeed, ME techniques and approaches would allow better reuse of the existing proven fragments of methods.